Edukasi Dan Pelatihan Pembuatan Minyak Rambut Herbal Berbahan Kemiri Untuk Pencegahan Rambut Rontok Di Kelurahan Paya Mabar, Kecamatan Stabat, Kabupaten Langkat - Hartini, Putri Tri; Lubis, Syahnan Aly; Nabila; Sry Ulina Karo-karo; Ziza Putri Aisyia Fauzi (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Hair loss is a common problem that impacts appearance and self-confidence, so a safe and effective natural solution is needed. Candlenut oil (Aleurites moluccanus) contains essential fatty acids and vitamin E which are beneficial in strengthening the hair and nourishing the scalp. This community service program was carried out in Paya Mabar Village, Stabat District, Langkat Regency, with the aim of increasing community knowledge and skills in making herbal hair oil made from candlenut. A total of 35 participants participated in the activity through counseling, demonstration, and hands-on practice, accompanied by evaluation using pre-test and post-test. The results showed an average knowledge increase of 38%, and 80% of participants succeeded in producing good quality hazelnut oil despite facing constraints on temperature regulation. This program proved effective in improving hair health literacy, natural ingredient processing skills, and opening up entrepreneurial opportunities based on local herbal products.